2003
DOI: 10.1590/s1516-89132003000300014
|View full text |Cite
|
Sign up to set email alerts
|

Fauna living in colonies of Mussismilia hispida (Verrill) (Cnidaria: Scleractinia) in four South-eastern Brazil islands

Abstract: Colonies of Mussismilia hispida were collected in four south-eastern Brazil islands and fixed in formalin. Volume, living and basal areas of each coral head were measured. Animals found over, under and inside the corals were sorted, resulting in 9657 specimens belonging to more than 130 taxa. The underside of the colonies was occupied by bivalves and colonial forms of sponges, bryozoans and ascidians. On the living surface, barnacles and cryptochiridean crabs were detected. The endolithic animals included poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
3
19
0
2
Order By: Relevance
“…1). We tested whether there is significant difference on the richness and abundance of crustaceans, the most frequent and abundant group living associated with coral colonies (Nogueira 2003;Stella et al 2011), and identified morphological characters (structural components) influencing them. (Cirano and Lessa 2007).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…1). We tested whether there is significant difference on the richness and abundance of crustaceans, the most frequent and abundant group living associated with coral colonies (Nogueira 2003;Stella et al 2011), and identified morphological characters (structural components) influencing them. (Cirano and Lessa 2007).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Remarks: Also known from various kinds of hard substrata, including corals (Veloso and Melo, 1993;Micheletti-Flores and NegreirosFransozo, 1999;Nogueira, 2003 (Melo, 1999;Rodríguez et al, 2005;Tagliafico et al, 2005;Lira et al, 2007).…”
Section: Pachycheles Monilifer (Dana 1852)mentioning
confidence: 99%
“…Many groups are associated with living corals, including non-colonial organisms such as flatworms, polychaetes, crustaceans, mollusks, echinoderms, sipunculans, bryozoans, and fishes, as well as colonial invertebrates such as sponges and ascidians (Young, 1986;Scott, 1987;Nogueira, 2003;OigmanPszczol and Creed, 2006;Garcia et al, 2008;Hoeksema et al, 2012). Living corals provide a hard substrate for the attachment of sessile bioerosion, which may not only reduce the strength of the coral skeleton, but may also kill portions of coral colonies (Kropp, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nogueira (2003) cited the occurrence of T. corallicola and O. hypostegus in colonies of Mussismilia hispida Verrill 1902. The identifications were possibly based on Melo (1996), in which there were only brief descriptions of the two species, cited as the only Brazilian representatives of the family.…”
Section: Discussionmentioning
confidence: 99%